Religiosity and Its Impact on Twitter Use and Viewing of Islamic Reality Television Shows among University Students in Malaysia (Pengaruh Keagamaan Terhadap Penggunaan Twitter dan Tontonan Program Realiti Islamik Dikalangan Pelajar Universiti di Malaysi) - Tengku Mohd Azzman Shariffadeen, Tengku Siti Aisha; A. Manaf, Aini Maznina (Journal of Islam in Asia (E-ISSN 2289-8077), 2018)
Islamic reality shows presents an alternative brand of entertainment for the Malaysian Muslim community. This television genre can also be perceived as an innovative form of da’wah. Through watching these shows, television viewers interested in faith-based content can increase their religious knowledge, educate themselves on the Islamic beliefs and practices, and identify with suitable Muslim role models featured on these shows. Thus, a major focus of this study is to examine use of social media and television viewing related to Islamic reality shows among Malaysian undergraduate students. The uses and gratification approach postulates that individual differences, such as viewer religiosity may influence media selection and use. Therefore, we propose that those who perceive religion more positively would be more interested in da’wah content, and would therefore be more likely to use Twitter to follow accounts related to the show. A cross-sectional survey is carried out among undergraduate students enrolled in introductory Islamic revealed knowledge and human sciences courses from the International Islamic University of Malaysia (N = 321). Among others, findings indicate that religious individuals are more likely to follow the Twitter account of their favorite Islamic reality show. Also, while viewer religiosity initially influenced frequency of viewing Islamic reality shows, those who tweeted frequently about the show is also more likely to view Islamic reality shows frequently. Finally, those who gratified their relaxation needs by following their favorite Islamic reality show personality on Twitter is more likely to view the show frequently. The repercussions of these findings on the role of religiosity and its effects on social media use and television viewing, based on the uses and gratification perspective is discussed in the paper. Keywords: Islamic Reality Shows, Religiosity, Television Viewing, Twitter Following Motivations, Uses and Gratification theory. Abstrak Program realiti Islamik merupakan alternatif buat penggemar rancangan hiburan berunsur keagamaan di Malaysia. Genre program televisyen ini juga boleh dipergunakan sebagai salah satu cara untuk berdakwah mengenai Islam. Dengan menonton program realiti Islamik, penonton boleh memupuk minat terhadap Islam, meningkatkan pengetahuan tentang Islam, mempelajari ilmu Islam dengan lebih mudah dan mengenali secara lebih dekat pendakwah muda yang terlibat dalam rancangan berkenaan. Oleh itu, salah satu objektif utama kajian ini ialah untuk meneliti penggunaan media sosial dan tontonan program realiti Islamik dikalangan pelajar universiti Malaysia. Bersandarkan theori uses and gratification, tingkahlaku dan latar belakang penonton memainkan peranan penting dalam mempengaruhi penggunaan media dikalangan individu. Dengan itu, kami menyarankan bahawa mereka yang mempunyai persepsi yang lebih positif terhadap agama akan mempunyai minat yang lebih mendalam terhadap agama, dan jesteru itu lebih cenderung untuk menggunakan Twitter untuk mendapatkan maklumat tentang program tersebut. Borang soal selidik telah disebarkan dikalangan pelajar Universiti Islam Antarabangsa Malaysia yang sedang mengikuti kursus asas dalam bidang sains sosial dan ilmu wahyu (N = 321). Dapatan kajian menunjukkan bahawa mereka yang berminat dengan agama lebih cenderung untuk mengikut akaun Twitter peserta program realiti Islamik. Juga, frekuensi menonton program realiti Islamik lebih dipengaruhi oleh kadar penggunaan Twitter berbanding dengan kadar keagamaan. Akhir sekali, mereka yang mempunya persepsi bahawa program realiti Islamik adalah program televisyen yang santai akan lebih cenderung untuk menonton program itu dimasa hadapan. Impak dapatan kajian terhadap theori uses and gratification serta pengaruh keagamaan terhadap pengunaaan media sosial dan kecenderungan untuk menonton program realiti Islamik di kaca televisyen akan dibincangkan dengan lebih mendalam. Kata Kunci: Program realiti Islamik, Keagamaan, Tontonan Televisyen, Motivasi Penggunaan Twitter, Theori Uses and Gratification.